A role for the terminal C5-C9 complement pathway in idiopathic pulmonary fibrosis - Sikkeland, Liv I. B.; Ueland, Thor; Lund, May B.; Durheim, Michael Thomas; Mollnes, Tom Eirik (Frontiers in Medicine, 2023)
Idiopathic pulmonary fibrosis (IPF) is a chronic progressive interstitial lung disease characterized by damage to the alveolar epithelium, leading to fibrosis and excessive accumulation of extracellular matrix in the interstitium of the lung. In the present study we performed high-resolution proteomic profiling of bronchoalveolar lavage (BAL) from IPF patients and controls, and found that the complement pathway was highly upregulated in IPF. The proteins C5, C6, C7, C8, and C9, all of which are part of the complement end product, TCC, were all upregulated. We also found that TCC levels were increased in plasma among IPF patients compared to controls, after adjustment for age, sex and BMI [mean (SD) 0.62 (0.24) vs. 0.33 (0.10), p = 0.031]. These findings suggest a role for the complement system in the pathogenesis of IPF.